2010
DOI: 10.1111/j.1365-2567.2010.03367.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neutrophil migration in mice by mouse formyl peptide receptors 1 and 2 dual agonist: indication of cross-desensitization in vivo

Abstract: Summary It has been reported that the stimulation of neutrophils with N‐formyl‐Met‐Leu‐Phe (fMLF), an agonist for formyl peptide receptor (Fpr) 1, renders cells unresponsive to other chemoattractants in vitro. This is known as cross‐desensitization, but its functional relevance in neutrophil migration in vivo has not been investigated. Here, we show that precedent stimulation of mouse neutrophils with compound 43, a non‐peptidyl agonist for mouse Fpr1 and Fpr2, rendered the cells unresponsive to a second stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…However, previous data showed that activation of FPRs inhibited migration of neutrophils through the desensitization of other chemokine receptors (29,30). As endogenous agonists, LXA4 and its metabolite 15-epi-LXA4 bind to FPRL1 and act as potent anti-inflammatory molecules that inhibit neutrophil chemotaxis, adherence, diapedesis, cytokine production, and superoxide generation (16,31).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous data showed that activation of FPRs inhibited migration of neutrophils through the desensitization of other chemokine receptors (29,30). As endogenous agonists, LXA4 and its metabolite 15-epi-LXA4 bind to FPRL1 and act as potent anti-inflammatory molecules that inhibit neutrophil chemotaxis, adherence, diapedesis, cytokine production, and superoxide generation (16,31).…”
Section: Discussionmentioning
confidence: 99%
“…Cpd43 was developed as a ligand for FPR2, and has been shown to inhibit neutrophil chemotaxis and markedly reduce mouse ear inflammation (Burli et al, 2006;Sogawa et al, 2011). Alterations in the structure of FPR2 prevent the action of Cpd43, suggesting the presence of specific sites on FPR2 with which Cpd43 interacts (Bena et al, 2012), although this has not been demonstrated physically, for example, using crystallography.Notably, in human neutrophils, Cpd43 has been reported to interact with both FPR1 and FPR2 (Forsman et al, 2011), suggesting that, in at least some conditions, it is a FPR1/2 dual agonist.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Cpd43 exerts anti-inflammatory effects in murine ear inflammation and air-pouch models, which require FPR2 (Burli et al, 2006;Dufton et al, 2010;Sogawa et al, 2011). Mutation studies have identified specific domains in FPR2, which are required for the action of Cpd43 (Bena et al, 2012), but in human neutrophils, Cpd43 has also been reported to interact with FPR1 (Forsman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of neutrophils through FPRs induces a variety of pro-inflammatory and antibacterial effector mechanisms including production of ROS, and release of antimicrobial peptides (AMPs) and hydrolytic enzymes from intracellular granules [20]. Furthermore, FPRs regulate the inflammatory reactions in neutrophils by modulating signaling through many other receptors in a process termed receptor cross-talk [21][22][23][24]. The role of FPRs in regulation of inflammation is highlighted by their suggested involvement in both systemic [25] and local [26][27][28] inflammatory responses.…”
Section: Of 52mentioning
confidence: 99%